ANALYSIS OF QUALITY ASSURANCE ON SISTEM INFORMASI ZAKAT (SIZAKAT) THROUGH SOFTWARE TESTING - Abdul Haris; Wisnu Jatmiko; Ari Wibisono (Jurnal Sistem Informasi, 2013)
Sistem Informasi Zakat (SIZakat) is a web-based information system that is used to assist in the management of zakat in Imam Bonjol Mosque Pondok Labu, South Jakarta. In this thesis, we conducted testing to the SIZakat application to know the quality and the feasibility. We conducted seven kinds of testing: Unit Testing, Integration Testing, Stress Testing, Load Testing, Testing SQL Injection, XSS Injection Testing and User Acceptance Testing. In addition to ensure the quality of SIZakat, the SIZakat test result is expected to be a reference for future quality improvement. Test results show that SIZakat have accurate functionalities, good security, and good performance.